Probabilistic Analysis of Various Hygroscopic Insulations : Impacts on Mould Growth and Energy Efficiency in Timber Frame Walls - Bayat Pour, Mohsen; Ranefjärd, Oskar; Niklewski, Jonas (Proceedings of CESBP 2025 - 6th Central European Symposium on Building Physics, 2026)
Highly insulated external wall assemblies are commonly employed to enhance building energy performance. However, research indicates that these assemblies may lead to moisture-related issues, such as mould growth. Recent studies suggest that the use of highly hygroscopic insulation materials, owing to their higher moisture buffering value, may mitigate relative humidity levels and consequently the risk of mould growth. In this study, the effect of choice of insulation on mould growth and heat flux is investigated through probabilistic hygrothermal simulation. Four insulation types— expanded polystyrene (EPS), mineral wool, wood fibre, and cellulose—are analysed under Stockholm’s climatic conditions. The probabilistic analysis accounts for uncertainties in material properties and boundary conditions, evaluating key parameters on wooden studs including mould growth and heat flux through insulation layers. Results indicate that the observed positive effect when using cellulose may be attributed to the material’s higher moisture buffer value—its ability to absorb significant water during transient peaks in relative humidity. Additionally, using wood fibre demonstrates that an enhanced moisture storage is ineffective if the material lacks adequate liquid water transport capability. Moreover, increased moisture buffering value in some insulation materials correlates with elevated heat flux, thereby reducing the wall assembly’s energy performance. These findings illustrate the necessity of balancing moisture safety, durability, and thermal performance to optimise the design of insulated wall assemblies.
Keywords: Hygroscopic properties; Insulation; Hygrothermal analysis; Probabilistic analysis; Mould growth; Heat flux